Analysis on fracture mechanics theory of roof cutting instability mechanism with large mining height face in shallow coal seam - Yang, Dengfeng (Frontiers in Earth Science, 2023)
The roof in fully-mechanized face of the shallow coal seam with large mining height is prone to form a "combined cantilever - articulated rock beam" structure, when the support resistance is insufficient, the “articulated rock beam” will sink, and make the "combined cantilever beam" rotate and fracture, it is easy to induce the sliding and instability of the "articulated rock beam", resulting in large-scale roof cutting and the support crushing. Taking the "combined cantilever beam" structure as the main research object, considering the mining damaged characteristics of cantilever beam rock stratum, the rock beam was regarded as a finite plate model with an edge crack of arbitrary dip angle, and a fracture mechanics model controlled by a set of structural planes were established, the instability conditions of rock beam and the main control factors were analyzed, and the method of determining the support resistance were discussed. The results show that the cantilever beam rotates and fractures, causes a chain reaction of the rock beam to fracture, the "combined cantilever beam" loses stability, with the increase of the length of the crack length and the crack dip angle, it is easier to penetrate the cantilever beam and cause roof instability. The necessary condition for rock beam instability was crack activation, and the sufficient condition was the airfoil branch crack propagate through the rock beam. The influence degree of each parameter on the support resistance was thus determined: crack length a > crack dip angle β > rock thickness h > weighting interval l. The theoretical analysis results were proved as reasonable by an in suit monitoring example of no. 22,310 working face in the Daliuta coal mine, China. On this basis, the reasonable value of support resistance was obtained. The above research conclusions provide a new method for researching the roof instability mechanism. It is also conducive to green and sustainable development of mines.